2016
DOI: 10.1021/acs.molpharmaceut.6b00335
|View full text |Cite
|
Sign up to set email alerts
|

PLGA Microparticles Entrapping Chitosan-Based Nanoparticles for the Ocular Delivery of Ranibizumab

Abstract: Age-related macular degeneration (AMD) is the leading cause of certified vision loss worldwide. The standard treatment for neovascular AMD involves repeated intravitreal injections of therapeutic proteins directed against vascular endothelial growth factor, such as ranibizumab. Biodegradable polymers, such as poly(lactic-co-glycolic acid) (PLGA), form delivery vehicles which can be used to treat posterior segment eye diseases, but suffer from poor protein loading and release. This work describes a 'system-with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 107 publications
3
52
0
Order By: Relevance
“…Elsaid et al [162] studied ranibizumab delivery using a "system-within-system" of PLGA-microspheres that contained nanoparticles. The polysaccharide nanoparticles were based on HA (MW 1500 kDa), chitosan (MW ≤ 400 kDa, degree of deacetylation 80-95%), and chitosan-N-acetyl-l-cysteine (CNAC).…”
Section: Micro and Nanoparticlesmentioning
confidence: 99%
“…Elsaid et al [162] studied ranibizumab delivery using a "system-within-system" of PLGA-microspheres that contained nanoparticles. The polysaccharide nanoparticles were based on HA (MW 1500 kDa), chitosan (MW ≤ 400 kDa, degree of deacetylation 80-95%), and chitosan-N-acetyl-l-cysteine (CNAC).…”
Section: Micro and Nanoparticlesmentioning
confidence: 99%
“…The same procedure has been followed for the preparation of the control probe, FITC-SWCNT-FA, and PPa-SWCNT-FA. Here, chitosan was chosen as it is a natural biocompatible biopolymer with favorable physicochemical properties and can potentially enhance the therapeutic effect [26,27]. Chitosan not only provides an appropriate biological interface to bind FA, PPa and FITC, but also provides a means to effectively disperse the as-prepared PPa/FITC-SWCNT-FA in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…31 Although the current study clearly demonstrates that intravenous delivery of PLGA-based RGD.Flt23k.NPs can effectively reduce CNV lesions, this nanoparticle delivery system can be further improved. Elsaid et al 32 developed PLGA-based nanoparticles with chitosan, improving the delivery of intravitreal ranibizumab (Lucentis) to CNV lesions so that it was 50% better than PLGA-based nanoparticles alone. In addition, we found that RGD.Flt23k.NP efficacy plateaus at a 30 mg dose, with a maximal reduction in CNV lesion size of 30%.…”
Section: Discussionmentioning
confidence: 99%